Traveling preferences in Madhya Pradesh post COVID-19 - Namrata Kishnani; Vivek Sharma (Journal of Enterprise and Development (JED), 2023)
Purpose — Travelling preferences and expectations play a dominant role in influencing tourists’ decision-making and choice of destination. Tourism sector is undergoing recovery from COVID-19, showing strong signs of change with the surge in domestic tourism in the Indian state of Madhya Pradesh. People’s priorities and expectations post-COVID-19 are going through continuous reformations under several socioeconomic and psychological makeup. Therefore, the research is conducted with the prerogative of understanding the traveling preferences of tourists post-COVID-19 towards the choice of tourism products.Method — The research follows a descriptive cum explanatory research design to study tourism prospects in Madhya Pradesh, known as Tiger state of India, which is popular for wilderness indigenous or heritage tourism. The data is collected through close-ended questionnaire from prominent tourist locations of Madhya Pradesh during 3-4 months of peak season and analyzed through descriptive statistics. Result — The study reflects the expectations of tourists concerning factors such as safety, hygiene, public works, quality of services, etc which affect their decision for choosing a destination and likelihood areas of expenditure.Contribution — The study is a unique account of research work on prospects of domestic tourism in Madhya Pradesh post-COVID-19. It fills the existing gap in the literature and will be facilitative for further studies and marketers alike for bringing resilience to the sector, understanding tourist’s preferences after any health or national emergencies.